Anaerobic Co-digestion with different concentrations of whey and cow dung in biogas production (LACCEI, 2024)
In this research, it was examined the potential of whey for the optimization of biogas production by anaerobic co – digestion with cow slurry. It was used a two-component multifactorial – design, where it was studied four batch type - biodigesters of 4 liters in laboratory scale with different whey concentrations (0%, 10%, 30%, 50%) and dilute cow dung in relation 1:1.5, each one in three replications. The experimentation was performed under temperature control of 35°C±2°C pH control between 6.4 to 6.9 by addition of NaOH 3N with an average of 7% of total solids and a holding time of 35 days. Below these conditions, the 2nd biodigester with 10% of whey, it was the one which generate the largest amount of biogas with 37.9 liters in total the 3rd biodigester, with 30% of whey generates 24.2 liters of biogas and the 4th biodigester, with 50% of whey generates 14.5 liters. Total solids reduction in biodigesters were 38.5%, 43.4%, 40.2% and 27.6% respectively. It was used Gompertz model, that allowed to found high grades of correlation grades oscillating between 86.295% y 94.268%. Therefore, it can be established, that the use of whey duplicates the biogas production until 52% and sets a limit of 30% (v/v) to obtain a good biogas production in batch type biodigesters.